Activation and Repression of Cellular Immediate Early Genes by Serum Response Factor Cofactors - Lee, Seung-Min (American Society for Biochemistry and Molecular Biology, 2010)
The induction of expression of many cellular immediate early genes (IEG) involves the transcription factor serum response factor (SRF). Two families of SRF coactivators have also been implicated in IEG induction, the ternary complex factors (TCFs), ELK1, Sap1, and Net, and the myocardin-related factors, MKL1 and MKL2. We found that serum induction of some SRF target genes is preferentially regulated by MKL1/2, whereas others are redundantly activated by both TCFs and MKL1/2. Yet ELK1 can also repress transcription. Binding of ELK1 and MKL1 to SRF has been found to be mutually exclusive in vitro, suggesting that ELK1 could repress expression of IEGs by blocking MKL1 binding. We characterized the in vivo binding of MKL1 and ELK1 to target genes and found an inverse relationship of serum-induced MKL1 binding and serum-decreased ELK1 binding. However, experiments with short hairpin RNA-mediated MKL1/2 depletion and expression of a nuclear MKL1 (N100) variant in stably transfected cells failed to alter ELK1 binding, suggesting that ELK1 binding to target genes is regulated independently of MKL1/2. Nevertheless, we found that short interfering RNA-mediated depletion of TCFs increased target gene expression in cells containing the N100 MKL1 activator, most notably in cells under continuous growth conditions. These results indicate that the TCFs can function both as activators and repressors of target gene expression depending upon the cellular growth conditions.